2020
DOI: 10.1111/rec.13311
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank offers potential for active restoration of mountain meadows

Abstract: The nitrogen‐fixing legume Lupinus polyphyllus invaded semi‐natural mountainous grasslands across Europe during the last decades. This invasion resulted in degraded habitats through changes in the structure and function of the mountain meadow vegetation. In our study, we analyzed (1) the effects of increasing cover of L. polyphyllus on the seed bank of mountain meadows, and (2) the potential of the seed bank of these stands for active restoration of mountain meadows in terms of species composition and number. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The vegetation types are characterized by the regular occurrence of the following plant species: Nardus grasslands— Nardus stricta , Potentilla erecta , and Galium saxatile ; mesic mountain meadows— Geranium sylvaticum , Trisetum flavescens , and Alchemilla monticola ; wet mountain meadows— Bistorta officinalis , Trollius europaeus , and Deschampsia cespitosa (Peppler‐Lisbach & Petersen 2001). The seed density of the soil seed bank (of all species and the target species) varies between the vegetation types with wet mountain hay meadows having higher seed densities than mesic mountain hay meadows and Nardus grasslands having the lowest density (Ludewig et al 2021). This might influence restoration success via seed bank activation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vegetation types are characterized by the regular occurrence of the following plant species: Nardus grasslands— Nardus stricta , Potentilla erecta , and Galium saxatile ; mesic mountain meadows— Geranium sylvaticum , Trisetum flavescens , and Alchemilla monticola ; wet mountain meadows— Bistorta officinalis , Trollius europaeus , and Deschampsia cespitosa (Peppler‐Lisbach & Petersen 2001). The seed density of the soil seed bank (of all species and the target species) varies between the vegetation types with wet mountain hay meadows having higher seed densities than mesic mountain hay meadows and Nardus grasslands having the lowest density (Ludewig et al 2021). This might influence restoration success via seed bank activation.…”
Section: Methodsmentioning
confidence: 99%
“…In all, the results presented here suggest that seed bank activation via large gaps does not guarantee success in promoting the establishment of target species in mountain meadows. Ludewig et al (2021) suggested that species missing from the soil bank could be actively introduced. Species diversity in grasslands can often be enhanced by additional introduction of seeds (Müller et al 2014) and green hay transfer is a very efficient method with regard to the high number of seeds that can be introduced (Scotton & Ševc ˇíkov a 2017).…”
Section: Effects Of the Restoration Measures On The Target Species Covermentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds mature throughout summer and stay in dormant stage throughout winter. The longevity of L. polyphyllus seed has been shown to be short-term in topsoil but if seeds are buried deeper, persistence is probably several years [48], and has been estimated to be over 50 years in controlled seed storage [49]. Garden lupin has the ability to utilize a whole growing season, as it is one of the first species to emerge and can reproduce until the end of growing season.…”
Section: Introductionmentioning
confidence: 99%
“…After stratification, samples were transferred to the greenhouse again and germination was observed until July 2016, when no more seeds germinated. More information on the vegetation and seed bank sampling can be found in Ludewig et al (2021). Plant nomenclature follows Jäger (2017).…”
Section: Samplingmentioning
confidence: 99%